2018
DOI: 10.1111/opec.12133
|View full text |Cite
|
Sign up to set email alerts
|

The effect of energy and urbanisation on carbon dioxide emissions: evidence from Ghana

Abstract: Concerned with the declining trend of renewable energy consumption as well as a change in the energy mix for electricity production amidst growing urban population and carbon dioxide (CO2) emissions in Ghana, this study examines the effect of urbanisation and energy on carbon dioxide emissions in Ghana within the framework of the Environmental Kuznets Curve (EKC) Hypothesis over the period 1971–2013. Estimation results from Fully Modified OLS confirm the presence of the EKC hypothesis over the period for Ghana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 76 publications
8
40
2
Order By: Relevance
“…According to the compact theory, the concentration of people and economic activities at the urban centers propels economies of scale (Elliott et al , 2014) which causes emission levels to decline. Empirically, Kwakwa and Alhassan (2018), Adom et al (2018) and Amuakwa-Mensah and Adom (2017) all reported urbanization has a positive effect on Ghana’s carbon emission. Also, Sheng and Guo (2016), Behera and Vishnu (2011) and Sinha et al (2017) found the emission effect of urbanization to be positive for China, India and N-11 economies, respectively.…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 94%
See 3 more Smart Citations
“…According to the compact theory, the concentration of people and economic activities at the urban centers propels economies of scale (Elliott et al , 2014) which causes emission levels to decline. Empirically, Kwakwa and Alhassan (2018), Adom et al (2018) and Amuakwa-Mensah and Adom (2017) all reported urbanization has a positive effect on Ghana’s carbon emission. Also, Sheng and Guo (2016), Behera and Vishnu (2011) and Sinha et al (2017) found the emission effect of urbanization to be positive for China, India and N-11 economies, respectively.…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 94%
“…The justification for this study is on the premise that initial studies that explored the effect of energy on carbon emissions focused largely on (primary/total) energy usage (Chebbi and Boujelbene, 2008; Kwakwa and Adu, 2016; Sun, 2012; Zhou et al , 2018). In recent times, however, some researchers have devoted attention to explore the effect of other energy indicators such as energy intensity/efficiency, renewable energy and nonrenewable energy usage (Kwakwa and Alhassan, 2018; Belaïd and Zrelli, 2016; Dogan and seker, 2016; Dar and Asif, 2019). These studies have been selective by choosing particular energy types for the studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, high consumption of energy increases carbon emissions. It is in this light that beyond looking at the relationship between energy and economic growth (Adom, 2013; Kwakwa, 2012; Kwakwa and Aboagye, 2014), some further look at the emission effect of energy (Kwakwa and Alhassan, 2018; Rahman et al , 2020; Aboagye, 2019; Kirikkaleli and Adebayo, 2021). Findings from such studies direct policymaking toward efficient energy consumption or the development of renewable energy resources.…”
Section: Literature Reviewmentioning
confidence: 99%